Virtual Content, Screen Time and Health - Qurat-ul Ain; Rashid Maqbool; Dr. Shahzad Farid; Saira Zafar (Journal of Information Management and Practices, 2023)
In today's digital era, the consumption of virtual content and screen time have become integral aspects of daily life. This study examines the interplay between virtual content consumption, screen time, and their impact on mental health outcomes, specifically focusing on depression, anxiety, and stress. The study used quantitative research approach. The study selected 384 participants using Cochran’s equation from three districts i.e. Okara, Pakpattan, and Sahiwal, of Division Sahiwal. Using simple random sampling, the researchers approached the selected respondents and collected data through face-to-face interview schedule of survey method. Statistical analysis, including correlation and regression analyses, was conducted to examine the interrelationships among these variables and explore potential gender differences. The study's findings show an association between mental health difficulties and screen time, with more screen time connected with higher stress, anxiety, and depression. These findings highlight the potential adverse effects of prolonged exposure to virtual content and extended screen time on psychological well-being.